COVID-19 Vaccine Hesitancy in Italy: Predictors of Acceptance, Fence Sitting and Refusal of the COVID-19 Vaccination - Cristina Zarbo; Valentina Candini; Clarissa Ferrari; Miriam d'Addazio; Gemma Calamandrei; Fabrizio Starace; Marta Caserotti; Teresa Gavaruzzi; Lorella Lotto; Alessandra Tasso; Manuel Zamparini; Giovanni de Girolamo (Frontiers Media S.A., 2022)
BackgroundThe hesitancy in taking the COVID-19 vaccine is a global challenge. The need to identify predictors of COVID-19 vaccine reluctance is critical. Our objectives were to evaluate sociodemographic, psychological, and behavioral factors, as well as attitudes and beliefs that influence COVID-19 vaccination hesitancy in the general population of Italy.MethodsA total of 2,015 people were assessed in two waves (March, April and May, 2021). Participants were divided into three groups: (1) individuals who accepted the vaccination ("accepters"); (2) individuals who refused the vaccination ("rejecters"); and (3) individuals who were uncertain about their attitudes toward the vaccination ("fence sitters"). Group comparisons were performed using ANOVA, the Kruskal-Wallis test and chi-square tests. The strength of the association between the groups and the participants' characteristics was analyzed using a series of multinomial logistic regression models with bootstrap internal validation (one for each factor).ResultsThe "fence sitters" group, when compared to the others, included individuals of younger age, lower educational level, and worsening economic situation in the previous 3 months. After controlling for sociodemographic factors, the following features emerged as the main risk factors for being "fence sitters" (compared with vaccine "accepters"): reporting lower levels of protective behaviors, trust in institutions and informational sources, frequency of use of informational sources, agreement with restrictions and higher conspirative mentality. Higher levels of COVID-19 perceived risk, trust in institutions and informational sources, frequency of use of informational sources, agreement with restrictions and protective behaviors were associated with a higher likelihood of becoming "fence sitters" rather than vaccine "rejecters."ConclusionsThe "fence sitters" profile revealed by this study is intriguing and should be the focus of public programmes aimed at improving adherence to the COVID-19 vaccination campaign.